New data on the irvinei group of Chydaeus of the Himalaya from Nepal and southern Tibet (Coleoptera, Carabidae, Harpalini) - Kataev, Boris M.; Schmidt, Joachim (Zootaxa, 2019)
Re-examination of the type series of Chydaeus irvinei (Andrewes, 1930) revealed that this species is based on two different taxa. It is re-described based on the lectotype and two paralectotypes from Gautsa in the Ngamo Chu Valley of southern Tibet between Sikkim and Bhutan. Chydaeus loeffleri (Jedlička, 1966) is treated as distinct species (not a synonym of Ch. irvinei) with two subspecies: the nominotypical one distributed in the Rolwaling Valley in eastern Central Nepal, and Ch. loeffleri tibetanus ssp. n. described on the basis of the paralectotype of Ch. irvinei from the Rongshar Valley in southern Tibet north west of the Rolwaling Himal. A new species Ch. soluensis sp. n., also similar to Ch. irvinei in appearance and genitalia, is described from the Solu Khumbu District of eastern Central Nepal (type locality: Lamjura Danda). In addition, a revised key to all species and subspecies of the irvinei group is provided.